The Effect Of Prescription Service Flow Optimization On Medication Waiting Time At Pharmaceutical Supplies Distribution Unit Of Regular Outpatient Dr. Moewardi Hospital - Gilchrist, Rafael Ega; Fildzah Ghassani, Yumma; Pratiwi, Retno; Ihsan Udin, Muhammad (Rumah Sakit Umum Daerah Dr. Moewardi, 2025)
Introduction Medication waiting time is one of the minimum pharmaceutical service standards in hospitals, which, if not achieved, can lead to patient dissatisfaction. Based on a field observation, several things hinder prescription services at the Pharmaceutical Supplies Distribution Unit of the regular outpatient of Dr. Moewardi Hospital. Optimization is carried out to reduce medication waiting times for drug services. Objective: To analyse the effect of optimization to medication waiting time at Pharmaceutical Supplies Distribution Unit of regular outpatient in Dr. Moewardi General Hospital Method The research method was conducted by comparing the average medication waiting time before and after optimization. Before a comparative test, a normality test was carried out with Kolmogorov – Smirnov. A T-test would be conducted if the data were distributed normally, if the data were not distributed normally, the Mann-Whitney test would be performed. Results The results showed a decrease in the waiting time for compounded medicines, both the time from the doctor ordering the prescriptions to the pharmacy validating the prescriptions (p=0.044), and the time from the pharmacy receiving the prescriptions until the medicines were ready (p=0.000). There was a decrease in the average waiting time for non-compounded medicines, the waiting time from the pharmacy receiving the prescriptions until the medicines were prepared, which was originally 45.54 minutes to 36.9 minutes after the service optimization was conducted. However, the decrease in time was not significantly different, both for the time from the doctor ordering the prescriptions to the pharmacy validating the prescriptions (p=0.386), and the time from the pharmacy receiving the prescriptions until the medicines were ready (p=0.305). Conclusion There is an effect of optimizing the flow of prescription services on waiting time of the compounded medicines at the UDPF of Regular Outpatient of Dr. Moewardi Hospital.